The Individual Grammar approach to foreign language learning. An idiolect-driven model for foreign language learners in independent settings (2016)
If, as Wittgenstein claimed, the limits of one’s language mean the limits of one’s world, it follows that the speaker’s idiolect comprise the boundaries of everyone’s linguistic competence, performance or verbal behaviour. That being the case, why has the idiolect not played a dominant role in foreign language teaching so far? This book makes a strong case to support the notion of foreign language learning without an a priori curriculum, institutional goals or textbooks’ pre-made itineraries; instead, its chief purpose is to empower learners with the tools to find and use their idiolects for accelerated L2 learning. The Individual Grammar Approach, unlike the received wisdom of a Chomskyan Universal Grammar, focuses on the individual’s idiolect to re-build, or re-encode a second idiolect in a foreign language. A bottom-up philosophy that will cer tainly determine the course of an entire research agenda based upon the paradigmatic shift of the individual, rather than that of the school, the teacher or the syllabus as the core of education. This work is a valuable reference for applied linguists, and cognitive scientists interested in language acquisition and learning, as well as teachers and researchers in education, as it sets out a forceful alternative to the traditional notions by developing a new theory of the L2 interlanguage, the mental lexicon, and the very concept of language mastery. If, as Wittgenstein claimed, the limits of one’s language mean the limits of one’s world, it follows that the speaker’s idiolect comprise the boundaries of everyone’s linguistic competence, performance or verbal behaviour.